Continuous ceramic fiber and preparation method and application thereof

By combining 3D printers with electrospinning technology, the direction and calcining conditions of ceramic fibers are accurately controlled, and the problem of disorder and continuity of ceramic fibers in the prior art is solved, and continuous ceramic fibers are efficiently prepared and their dielectric properties are fully utilized.

CN119736735APending Publication Date: 2025-04-01FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411953412.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing electrospinning technology is difficult to effectively control the structure of ceramic fibers, resulting in disordered fibers and difficulty in preparing single nanofibers, and it is easy to destroy the continuous structure during the preparation process.

Method used

By combining a direct-write 3D printer with electrospinning, the electrospinning needle is controlled to move according to the 3D printing model, accurately control the direction of the ceramic fibers and maintain its continuity, and a program of heating and calcining is used to achieve efficient preparation of continuous ceramic fibers.

Benefits of technology

The orderly preparation and continuous structure of ceramic fibers are achieved, the high dielectric properties of ceramics are fully utilized, the process is simplified, and the process is easy to be applied on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005215360820000011
    Figure HDA0005215360820000011
  • Figure HDA0005215360820000012
    Figure HDA0005215360820000012
  • Figure HDA0005215360820000021
    Figure HDA0005215360820000021
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic fibers, in particular to a continuous ceramic fiber and a preparation method and application thereof.The continuous ceramic fiber is at least prepared from, by mass, 0-50% of nanoscale ceramic filler, 0-1% of thickening agent and the balance solvent, and the content of the nanoscale ceramic filler and the content of the thickening agent are not zero. The direct-writing 3D printer and electrostatic spinning are creatively combined, so that the electrostatic spinning needle head moves according to the 3D printing model, the trend of the ceramic fibers is controlled, the ceramic fibers are kept continuous, and the subsequent application effect is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic fibers, in particular to a continuous ceramic fiber and a preparation method and application thereof. Background Art

[0002] Continuous ceramic fiber is a high-performance fiber material that plays a key role in enhancing dielectric properties in polymer-based composites and is essential for improving the energy storage density of composites. It has broad application prospects in hybrid vehicles, flexible wearable devices, pulse power devices, curved screens, and other fields.

[0003] Most of the methods for preparing continuous ceramic fibers are electrospinning. The structure of traditional electrospinning fibers is disordered. Due to the unstable "whipping" state during the spinning process, the received fibers are often disordered, making it difficult to prepare a single nanofiber. In addition, the material for collecting the electrospinning product needs to be coated on a roller, most of which are aluminum foil, which limits the electrospinning product to a certain extent, and peeling the electrospinning product on the aluminum foil will also cause the destruction of the continuous structure. A method for preparing uniform and dense high-temperature continuous zirconia filaments disclosed in a Chinese patent application (authorization announcement number CN115233336B) utilizes the very slow growth characteristics of mullite below 1600°C. The obtained continuous zirconia filaments have uniform diameters, small grain sizes, high densification, strength, and modulus, but the overall preparation process is complicated and not easy to achieve large-scale industrial application production. Summary of the invention

[0004] In order to solve the above problems, the present invention creatively combines a direct-write 3D printer with electrospinning, so that the electrospinning needle moves according to the 3D printing model, controls the direction of the ceramic fibers and maintains the continuity of the ceramic fibers, thereby ensuring the subsequent application effect.

[0005] On one hand, the present invention provides a continuous ceramic fiber, wherein the raw materials for its preparation at least include, by mass percentage: 0-50% nano-grade ceramic filler, 0-1% thickener, and solvent to make up the balance, wherein the contents of the nano-grade ceramic filler, the nano-grade ceramic filler and the thickener are not zero.

[0006] As a preferred technical solution, the raw materials for preparing the continuous ceramic fiber include at least 20-50% of nano-grade ceramic filler, 0.01-0.1% of thickener, and the balance of solvent, by mass percentage.

[0007] Further preferably, the mass ratio of the nano-scale ceramic filler, thickener and solvent is (4-8):8:0.6.

[0008] As a preferred technical solution, the particle size of the nano-scale ceramic filler is ≤200nm.

[0009] Preferably, the particle size of the nano-scale ceramic filler is 50-100 nm, preferably 100 nm.

[0010] As a preferred technical solution, the nano-scale ceramic filler is selected from at least one of nano-barium titanate, nano-strontium titanate, nano-strontium barium titanate, nano-lead zirconate titanate, and nano-copper calcium titanate, preferably nano-barium titanate.

[0011] As a preferred technical solution, the thickener at least includes polyvinyl pyrrolidone.

[0012] Preferably, the K value of the polyvinyl pyrrolidone is ≥60, preferably 88-96 (average molecular weight is 1,300,000).

[0013] Among them: PVP (polyvinyl pyrrolidone) is graded according to its average molecular weight, which is usually expressed by K value. Different K values ​​represent the corresponding PVP average molecular weight range. K value is actually a characteristic value related to the relative viscosity of PVP aqueous solution. Generally, the larger the K value, the greater its viscosity.

[0014] As a preferred technical solution, the solvent is selected from at least one of water, alcohol, amine, and halogenated hydrocarbon, preferably ethanol.

[0015] Another aspect of the present invention provides a method for preparing continuous ceramic fibers, comprising at least the following steps:

[0016] (1) dispersing a nano-scale ceramic filler in a solvent, adding a thickener in batches under stirring, and after all the thickener is added, continuing stirring, and ultrasonically treating to obtain a nano-scale ceramic filler dispersion;

[0017] (2) Controlling the electrospinning conditions, the nano-scale ceramic filler dispersion is continuously, uniformly and orderly electrospun onto a collecting plate through a 3D printer control program to obtain ceramic fibers, and continuous ceramic fibers are obtained after calcination.

[0018] As a preferred technical solution, the stirring time is 1-3 hours, preferably 2 hours.

[0019] As a preferred technical solution, the ultrasonic treatment time is 10-60 min, preferably 30 min.

[0020] As a preferred technical solution, the electrospinning conditions are: the electrospinning syringe is equipped with a 10-30G needle, the voltage is 10-20kV, the air pressure is 0.05-0.3MPa, and the vertical distance between the needle and the collecting plate is 5-10cm.

[0021] Preferably, the electrospinning conditions are: the electrospinning syringe is equipped with a 24G needle, the voltage is 15 kV, the air pressure is 0.1 MPa, and the vertical distance between the needle and the collecting plate is 8 cm.

[0022] As a preferred technical solution, the collecting plate is a quartz glass plate.

[0023] As a preferred technical solution, the calcination is a programmed temperature calcination, and the programmed temperature calcination conditions are: heating from 10-30°C to 100-360°C at 4-6°C / min, and keeping warm for 15-40min; heating to 600-800°C at 1-2°C / min, and keeping warm for 2-4h; heating to 1000-1500°C at 2-4°C / min, and keeping warm for 4-6h.

[0024] Preferably, the programmed temperature calcination conditions are: heating from 10-30°C to 100-200°C at 5°C / min, and keeping warm for 15-40min; heating to 650-750°C at 1°C / min, and keeping warm for 2-4h; heating to 1200-1500°C at 3°C / min, and keeping warm for 4-6h.

[0025] Further preferably, the programmed temperature calcination conditions are: heating from 25°C to 150°C at 5°C / min, keeping warm for 30 minutes; heating to 700°C at 1°C / min, keeping warm for 3 hours; heating to 1200°C at 3°C, keeping warm for 5 hours.

[0026] The present invention prepares nano-scale ceramic fillers into continuous ceramic fibers by optimizing the electrostatic spinning process in conjunction with the 3D printer control program, accurately controls the direction of the ceramic fibers, and can orderly prepare multi-layer continuous fibers, overcoming the defects of the existing electrostatic spinning technology (mainly collecting fibers by roller type) that the structure of the fibers cannot be effectively controlled. In particular, the selection of each raw material in the nano-scale ceramic filler dispersion, the control of the amount of addition, and the coordination of the preparation process are optimized, and the efficient preparation of continuous fibrous ceramic fibers is achieved by using programmed temperature calcination under suitable electrostatic spinning conditions. Further, by controlling the programmed temperature calcination conditions, it is ensured that the prepared continuous ceramic fibers remain continuous, and the grain boundaries between the complete ceramic particles and the ceramic particles are maintained, which helps to give full play to the high dielectric properties of ceramics.

[0027] A third aspect of the present invention provides an application of a continuous ceramic fiber for use in the preparation of a continuous ceramic fiber / polymer-based composite material.

[0028] As a preferred technical solution, the preparation method of the continuous ceramic fiber / polymer-based composite material comprises at least the following steps: dissolving the polymer matrix in an organic solvent to obtain a polymer solution, loading the polymer solution into an electrospinning syringe, selecting an 18-24G needle, passing an 8-12kV voltage and an 0.1-0.5MPa air pressure, and keeping the needle 5-10cm away from the continuous ceramic fiber. The electrospinning path is determined by a 3D printer control program so that the polymer solution is evenly and orderly electrospun on the continuous ceramic fiber, and the continuous ceramic fiber / polymer-based composite material is obtained after heating and curing.

[0029] As a preferred technical solution, the polymer matrix is ​​selected from one of polyimide, polyethylene, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl alcohol, polyurethane, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene, and polyetherimide, preferably polyimide.

[0030] As a preferred technical solution, the organic solvent is selected from at least one of N,N-dimethylacetamide (DMAC), N,N-dimethylformamide, and N-vinylpyrrolidone, preferably N,N-dimethylacetamide.

[0031] As a preferred technical solution, the mass proportion of the polymer matrix in the polymer solution is 20-100%, preferably 50-100%, and most preferably 66.7%.

[0032] As a preferred technical solution, the conditions for heating and curing are: heating from 10-30°C to 100°C for 20-40 minutes, keeping warm for 15-40 minutes; continuing to heat up for 20-40 minutes to 150°C, keeping warm for 30-50 minutes; continuing to heat up for 50-90 minutes to 260°C, keeping warm for 15-40 minutes.

[0033] Preferably, the temperature-raising curing conditions are: raising the temperature from 25°C to 100°C for 30 minutes, and keeping the temperature for 30 minutes; continuing to raise the temperature to 150°C for 30 minutes, and keeping the temperature for 40 minutes; continuing to raise the temperature to 260°C for 60 minutes, and keeping the temperature for 30 minutes.

[0034] The present invention directly composites the polymer solution with continuous ceramic fibers by electrostatic spinning in conjunction with a 3D printer control program, thereby avoiding ceramic fiber transfer, effectively maintaining the continuous structure of the fibers, giving full play to the dielectric properties of the ceramics, and thus giving the continuous ceramic fiber / polymer-based composite material excellent dielectric properties.

[0035] The preparation method of the continuous ceramic fiber / polymer-based composite material provided by the present invention is simple. The continuous ceramic fiber is composited with the polymer without considering the dispersion of the ceramic, which greatly simplifies the process and is easy to realize large-scale industrial application and production.

[0036] The continuous ceramic fiber / polymer-based composite material provided by the present invention has high dielectric strength and flexibility, can be widely used in wearable electronics, energy storage, electronic and electrical industries, and has extremely high market promotion value.

[0037] A fourth aspect of the present invention provides a flexible wearable device comprising a continuous ceramic fiber / polymer-based composite material and a sensor.

[0038] Beneficial Effects

[0039] 1. The present invention creatively combines a direct-write 3D printer with electrospinning, so that the electrospinning needle moves according to the 3D printing model, controls the direction of the ceramic fibers and maintains the continuity of the ceramic fibers, thereby ensuring the subsequent application effect.

[0040] 2. The present invention optimizes the electrospinning process and cooperates with the 3D printer control program to prepare nano-scale ceramic fillers into continuous ceramic fibers, accurately controls the direction of the ceramic fibers, and can prepare multiple layers of continuous fibers in an orderly manner.

[0041] 3. The present invention optimizes the selection of various raw materials in the nano-ceramic filler dispersion, the control of the addition amount and the coordination of the preparation process, and adopts programmed temperature calcination under appropriate electrospinning conditions to achieve efficient preparation of continuous fibrous ceramic fibers. Furthermore, by controlling the programmed temperature calcination conditions, it is ensured that the prepared ceramic fibers remain continuous, and the complete ceramic particles and the grain boundaries between the ceramic particles are maintained, which helps to give full play to the high dielectric properties of the ceramics.

[0042] 4. The present invention avoids the transfer of ceramic fibers by directly compounding the polymer solution with continuous ceramic fibers through electrostatic spinning in conjunction with a 3D printer control program, effectively maintains the continuous structure of the fibers, gives full play to the dielectric properties of ceramics, and thereby gives the continuous ceramic fiber / polymer-based composite material excellent dielectric properties.

[0043] 5. The preparation method of the continuous ceramic fiber / polymer-based composite material provided by the present invention is simple. The continuous ceramic fiber is composited with the polymer, and there is no need to consider the dispersion of the ceramic, which greatly simplifies the process and is easy to realize large-scale industrial application and production.

[0044] 6. The continuous ceramic fiber / polymer-based composite material provided by the present invention has a high dielectric constant and flexibility, can be widely used in wearable electronics, energy storage, electronic and electrical industries, and has extremely high market promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a surface SEM characterization image of the continuous ceramic fiber provided in Example 1 of the present invention.

[0046] Figure 2 This is a surface SEM characterization image of the continuous ceramic fiber provided in Example 2 of the present invention.

[0047] Figure 3 This is a surface SEM characterization image of the continuous ceramic fiber provided in Example 3 of the present invention.

[0048] Figure 4 This is a surface SEM characterization image of the continuous ceramic fiber / polymer-based composite material provided in Example 5 of the present invention.

[0049] Figure 5 This is a graph showing the dielectric properties test results of the continuous ceramic fiber / polymer matrix composite material provided in Example 1.

[0050] Figure 6 This is a graph showing the dielectric properties test results of the continuous ceramic fiber / polymer matrix composite material provided in Example 4. DETAILED DESCRIPTION

[0051] Example 1

[0052] Embodiment 1 of the present invention provides continuous ceramic fibers. The raw materials for preparing the continuous ceramic fibers include, by mass percentage, 31.7% of nano-grade ceramic filler, 0.05% of thickener, and the rest of the amount of solvent.

[0053] The particle size of the nano-scale ceramic filler is 100 nm.

[0054] The nano-scale ceramic filler is nano-barium titanate, which comes from Shanghai McLean Biochemical Technology Co., Ltd.

[0055] The thickener is polyvinyl pyrrolidone, the K value of the polyvinyl pyrrolidone is 88-96 (average molecular weight is 1300000), and it is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0056] The solvent is ethanol.

[0057] On the other hand, Example 1 of the present invention provides a method for preparing continuous ceramic fibers, comprising the following steps: (1) dispersing a nano-scale ceramic filler in a solvent, adding a thickener in 6 equal batches under stirring, continuing stirring after all the thickener has been added, and ultrasonically treating to obtain a nano-scale ceramic filler dispersion; (2) controlling the electrospinning conditions, and continuously and uniformly electrospinning the nano-scale ceramic filler dispersion onto a collecting plate through a 3D printer control program to obtain ceramic fibers, and obtaining continuous ceramic fibers after calcination.

[0058] The stirring time is continued for 2 hours.

[0059] The ultrasonic treatment time is 30 min.

[0060] The electrospinning conditions are as follows: the electrospinning syringe is equipped with a 24G needle, the voltage is 15 kV, the air pressure is 0.1 MPa, and the vertical distance between the needle and the collecting plate is 8 cm.

[0061] The collecting plate is a quartz glass plate with a smooth surface and a size of 50 mm×50 mm.

[0062] The calcination is a programmed temperature calcination, and the programmed temperature calcination conditions are: heating from 25°C to 150°C at 5°C / min, keeping warm for 30 minutes; heating to 700°C at 1°C / min, keeping warm for 3 hours; heating to 1200°C at 3°C / min, keeping warm for 5 hours.

[0063] The third aspect of Example 1 of the present invention provides a continuous ceramic fiber / polymer-based composite material.

[0064] The preparation method of the continuous ceramic fiber / polymer-based composite material comprises the following steps: dissolving a polymer matrix in an organic solvent to obtain a polymer solution, loading the polymer solution into an electrospinning syringe, selecting a 20G needle, passing a 9kV voltage and a 0.25MPa air pressure, and placing the needle 8cm away from the continuous ceramic fiber (attached to the surface of a quartz glass plate), and controlling the polymer solution by a 3D printer to uniformly electrospin the polymer solution on the continuous ceramic fiber, and heating and curing to obtain the continuous ceramic fiber / polymer-based composite material.

[0065] The polymer matrix is ​​polyimide, model PAA-215, purchased from Dongguan Donglin Polymer Materials Co., Ltd.

[0066] The organic solvent is N,N-dimethylacetamide.

[0067] The mass proportion of the polymer matrix in the polymer solution is 66.7%.

[0068] The temperature-raising curing conditions are as follows: raising the temperature from 25° C. to 100° C. for 30 minutes and keeping the temperature for 30 minutes; continuing to raise the temperature to 150° C. for 30 minutes and keeping the temperature for 40 minutes; continuing to raise the temperature to 260° C. for 60 minutes and keeping the temperature for 30 minutes.

[0069] Example 2

[0070] Example 2 of the present invention provides continuous ceramic fibers, a preparation method thereof, and a continuous ceramic fiber / polymer-based composite material. Its specific implementation method is the same as that of Example 1, except that, by mass percentage, its preparation raw materials include: 48.2% nano-grade ceramic filler, 0.05% thickener, and the balance made up of solvent.

[0071] Example 3

[0072] Example 3 of the present invention provides continuous ceramic fibers, a preparation method thereof, and a continuous ceramic fiber / polymer-based composite material. Its specific implementation method is the same as that of Example 1, except that, in terms of mass percentage, the preparation raw materials include: 51.1% nano-ceramic filler, 0.05% thickener, and the balance solvent. The electrospinning conditions are: the electrospinning syringe is equipped with a 24G needle, the voltage is 10kV, the air pressure is 0.1MPa, and the vertical distance between the needle and the collecting plate is 8cm.

[0073] Example 4

[0074] Example 4 of the present invention provides continuous ceramic fibers, a preparation method thereof, and a continuous ceramic fiber / polymer-based composite material. The specific implementation manner is the same as that of Example 1, except that the programmed temperature calcination conditions are: heating from 25°C to 150°C at 5°C / min, and keeping warm for 30 minutes; heating to 700°C at 3°C / min, and keeping warm for 3 hours; heating to 1200°C at 3°C / min, and keeping warm for 2 hours.

[0075] Example 5

[0076] Example 5 of the present invention provides continuous ceramic fibers and a preparation method thereof and a continuous ceramic fiber / polymer-based composite material. Its specific implementation is the same as that of Example 1, except that the collecting plate is an alumina plate with an uneven surface and a size of 50 mm×50 mm.

[0077] Performance Testing

[0078] 1. The surface of the continuous ceramic fibers provided in Examples 1-3 was characterized by SEM. The results are shown in Figure 1-3 ; The surface of the continuous ceramic fiber / polymer matrix composite material provided in Example 5 was characterized by SEM, and the results are shown in Figure 4 ; It can be seen from the SEM image that the continuous ceramic fiber prepared in Example 1 is fibrous and continuous; the continuous ceramic fiber particles prepared in Example 2 account for the main part; the continuous ceramic fiber prepared in Example 3 has too many barium titanate particles and less barium titanate fibers; the continuous ceramic fiber / polymer-based composite material provided in Example 5 has a substrate surface structure, which makes the ceramic fiber discontinuous.

[0079] 2. The dielectric properties of the continuous ceramic fiber / polymer matrix composite materials provided in Example 1 and Example 4 were tested. The test results are shown in Figure 5 , Figure 6 The results show that the dielectric constant of the continuous ceramic fiber / polymer matrix composite material provided in Example 1 reaches 62.7 at 40 Hz, and the dielectric loss is between 40 and 10 5 Hz is lower than 0.08, and the dielectric properties of the continuous ceramic fiber / polymer matrix composite material provided in Example 4 are reduced.

Claims

1. A continuous ceramic fiber, characterized in that: The raw materials for its preparation at least include, by mass percentage: 0-50% of nano-grade ceramic filler, 0-1% of thickener, and the balance of solvent, wherein the contents of the nano-grade ceramic filler and the thickener are not zero.

2. The continuous ceramic fiber according to claim 1, characterized in that The particle size of the nano-scale ceramic filler is ≤200nm, and the nano-scale ceramic filler is selected from at least one of nano-barium titanate, nano-strontium titanate, nano-strontium barium titanate, nano-lead zirconate titanate, and nano-copper calcium titanate.

3. The continuous ceramic fiber according to claim 1, characterized in that The thickener at least comprises polyvinyl pyrrolidone, and the K value of the polyvinyl pyrrolidone is ≥60.

4. The continuous ceramic fiber according to claim 1, characterized in that The solvent is selected from at least one of water, alcohol, amine and halogenated hydrocarbon.

5. A method for preparing a continuous ceramic fiber according to any one of claims 1 to 4, characterized in that: At least the following steps are included: (1) dispersing a nano-scale ceramic filler in a solvent, adding a thickener in batches under stirring, and after all the thickener is added, continuing stirring, and ultrasonically treating to obtain a nano-scale ceramic filler dispersion; (2) Controlling the electrospinning conditions, the nano-scale ceramic filler dispersion is continuously and uniformly electrospun onto a collecting plate through a 3D printer control program to obtain ceramic fibers, and continuous ceramic fibers are obtained after calcination.

6. The method for preparing continuous ceramic fibers according to claim 5, characterized in that: The electrospinning conditions are as follows: the electrospinning syringe is equipped with a 10-30G needle, the voltage is 10-20 kV, the air pressure is 0.05-0.3 MPa, and the vertical distance between the needle and the collecting plate is 5-10 cm.

7. The method for preparing continuous ceramic fibers according to claim 5, characterized in that: The calcination is programmed temperature calcination, and the programmed temperature calcination conditions are: heating from 10-30°C to 100-360°C at 4-6°C / min, and keeping warm for 15-40min; heating to 600-800°C at 1-2°C / min, and keeping warm for 2-4h; heating to 1000-1500°C at 2-4°C / min, and keeping warm for 4-6h.

8. An application of the continuous ceramic fiber according to any one of claims 1 to 4, characterized in that: Applied to the preparation of continuous ceramic fiber / polymer matrix composites.

9. The use of the continuous ceramic fiber according to claim 8, characterized in that: The method for preparing the continuous ceramic fiber / polymer-based composite material comprises at least The method comprises the following steps: dissolving a polymer matrix in an organic solvent to obtain a polymer solution, loading the polymer solution into an electrospinning syringe, selecting an 18-24G needle, passing an 8-12kV voltage and an 0.1-0.5MPa air pressure, keeping the needle 5-10cm away from the continuous ceramic fiber, and determining the electrospinning path through a 3D printer control program so that the polymer solution is electrospun uniformly and orderly on the continuous ceramic fiber, and obtaining a continuous ceramic fiber / polymer matrix composite material after heating and curing.

10. The use of the continuous ceramic fiber according to claim 9, characterized in that: The mass proportion of the polymer matrix in the polymer solution is 20-100%.

Citation Information

Patent Citations

  • A method for preparing uniform and dense high-temperature continuous zirconia filament

    CN115233336B